The importance of pyramidal tract integrity for cortical plasticity and related functionality in patients with multiple sclerosis - Balloff, Carolin; Albrecht, Philipp; Stucke, Arved-Sebastian; Scala, Lina; Novello, Sveva; Hartmann, Christian Johannes; Meuth, Sven Günther; Schnitzler, Alfons; Penner, Iris-Katharina; Groiss, Stefan Jun (Frontiers in Neurology, 2023)
Background Cortical plasticity induced by quadripulse stimulation (QPS) has been shown to correlate with cognitive functions in patients with relapsing-remitting multiple sclerosis (RRMS) and to not be reduced compared to healthy controls (HCs). Objective This study aimed to compare the degree of QPS-induced plasticity between different subtypes of multiple sclerosis (MS) and HCs and to investigate the association of the degree of plasticity with motor and cognitive functions. We expected lower levels of plasticity in patients with progressive MS (PMS) but not RRMS compared to HCs. Furthermore, we expected to find positive correlations with cognitive and motor performance in patients with MS. Methods QPS-induced plasticity was compared between 34 patients with PMS, 30 patients with RRMS, and 30 HCs using linear mixed-effects models. The degree of QPS-induced cortical plasticity was correlated with various motor and cognitive outcomes. Results There were no differences regarding the degree of QPS-induced cortical plasticity between HCs and patients with RRMS (p = 0.86) and PMS (p = 0.18). However, we only found correlations between the level of induced plasticity and both motor and cognitive functions in patients with intact corticospinal tract integrity. Exploratory analysis revealed significantly reduced QPS-induced plasticity in patients with damage compared to intact corticospinal tract integrity (p < 0.001). Conclusion Our study supports the notion of pyramidal tract integrity being of more relevance for QPS-induced cortical plasticity in MS and related functional significance than the type of disease.